Strategi Pemasaran Air Minum Dalam Kemasan (AMDK) Merk Mox Pada Toko Mario Oxi Desa Tarailu Kecamatan Sampaga - Fajariani, Nur (Forecasting : Jurnal Ilmiah Ilmu Manajemen, 2022)
This research is entitled Marketing Strategy of Mox Brand Bottled Drinking Water (AMDK) at Mario Oxi Shop, Tarailu Village, Sampaga District. The purpose of this research is to find out the marketing strategy applied by Mario Oxi Shop in an effort to market its Mox brand bottled drinking water (AMDK) products. The types of data used in this study include quantitative data and qualitative data. Sources of data in this study include primary data and secondary data. The subject of this research is Mario Oxi Store, while the object of this research is the marketing strategy applied by Mario Oxi Store in an effort to market its products. The data analysis technique used in this research is a qualitative descriptive technique. Based on the results of observations made by the author, there is a picture of the environment faced by Mario Oxi Stores both from within the company itself (strengths and weaknesses) and from outside the company environment (opportunities and threats). Shop Manager Mario Oxi in carrying out the company's business activities must be able to take advantage of internal conditions and external conditions in the development of the company, because the prospects of a company cannot be separated from an understanding of the existing environment, both the internal environment and the company's external environment, because the influence of the environment is constantly interacting.